Factors interfering with the attribute longitudinality in the primary health care: an integrative review - Cristiane Cardoso de Paula; Clarissa Bohrer da Silva; Elisa Gomes Nazário; Tamiris Ferreira; Maria Denise Schimith; Stela Maris de Mello Padoin (Universidade Federal de Goias, 2015)
Our objective was to assess the evidence available in the literature about factors interfering with the primary health care attribute longitudinality. This is an integrative review, developed in May of 2014, on the following electronic databases: LILACS, PubMed and Scopus. We used the descriptors "primary health care" and "continuity of patient care". In total, 16 articles were fully assessed. We organized the data in accordance with care aspects longitudinality (structure and performance) and we divided the identified factors in accordance with the attribute interference (favoring or disfavoring). The evidence offer aids to compose a global panorama of interfering factors on longitudinality, reinforcing the value of its interpersonal relationships and minimizing gaps in the organization of health services. The prevalence of descriptive studies suggests the need to strengthen the construction of knowledge with studies of higher evidence level.